Addressing Vulnerability in East Asia : A Regional Study - World Bank (Washington, DC, 2012)
The East Asian and Pacific region has achieved tremendous progress in poverty reduction in recent years. However, further progress in poverty reduction may be undermined by the high levels of vulnerability in many countries across the region. The term vulnerability is viewed from an economic context, where it is conceived as the likelihood of suffering from future deteriorations in standard of living which may result in a state of poverty, or inability to meet basic needs. Therefore, vulnerability is stated as an ex-ante measure of well-being, reflecting not so much how well off a household (or an individual) currently is, but what its future prospects are. In thinking about poverty and vulnerability, it is important to realize that there are two groups of households: a) those who are vulnerable to transitory poverty if exposed to adverse shocks; and b) those who are structurally or chronically poor-many of those households have been affected by shocks in the past, and have limited long-term income generating capacity. To better protect household from shocks one must also better understand how households face and manage risks.